Shaping Sangihe’s Marine Tourism Destination Image: A Multi-Stakeholder Perspective - Mozes, Getruida Nita; Laluas, Efraim (Institut Pariwisata dan Bisnis Internasional, 2025)
Destination image is a critical determinant of tourist attraction and long-term competitiveness, particularly for emerging marine tourism destinations. Sangihe Island, located in Indonesia’s outer island region, possesses diverse marine and coastal resources but faces challenges in forming a strong and consistent tourism destination image. Previous studies on destination image development have predominantly focused on marketing and promotional strategies, with limited attention to the role of multi-stakeholder collaboration in shaping image formation from the tourist’s perspective. This study aims to analyze how various stakeholders contribute to shaping Sangihe’s marine tourism destination image as perceived by tourists. This research employs a qualitative descriptive approach through in-depth interviews with tourists and key stakeholders, including government institutions, local communities, tourism businesses, media actors, and academic representatives. The analysis emphasizes key destination image dimensions from the tourist perspective, namely marine and natural attractions, environmental quality, service experience, accessibility, safety, and destination promotion. Data were analyzed thematically to explore stakeholder roles, interactions, and their influence on tourist perceptions. The findings indicate that effective collaboration among stakeholders plays a significant role in strengthening positive destination perceptions and enhancing tourist satisfaction. Integrated governance, active community participation, and coherent promotional narratives contribute to a favorable marine tourism image. However, fragmented coordination and unequal stakeholder involvement can weaken image consistency and visitor experience. This study contributes theoretically by integrating destination image and stakeholder collaboration frameworks within a marine tourism context. Practically, the findings provide strategic insights for destination managers and policymakers to reinforce collaborative approaches as a foundation for sustainable marine tourism development in small island destinations.